The Impact of Political Instability on Exchange Rate in South Africa: An Econometric Modelling - Munzhelele Tshilidzi; Jeke L (Indonesian Journal of Islamic Economics and Finance)
The study examines the impact of political instability on exchange rates while adjusting for economic growth and real interest rates from 1989 to 2020. After applying the VECM model, the findings indicate a short-term correlation between exchange rates and political instability. The results of the Granger causality suggest that exchange rate fluctuations and inflation rates are not directly caused by political instability. Additionally, the ARIMA model results indicate that political instability in the long run should be anticipated to cause minor fluctuations in exchange rates. Political unrest is forecast to level off between 2021 and 2040, with a subsequent increase in the exchange rate expected. It is recommended that policymakers deal with macroeconomic conditions that affect exchange rates, such as interest rates, to stabilize the economy and avoid excessive currency appreciation or depreciation.